Inventarisasi, kunci identifikasi, pemetaan, dan rekomendasi pengelolaan jenis-jenis bambu di ecology park, pusat konservasi tumbuhan, kebun raya–LIPI, Kabupaten Bogor, Jawa Barat - Damayanto, I Putu Gede P.; Mulyani, Sri; Wahidah, Baiq Farhatul (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019, 2019)
Inventory, identification key, mapping, and management recommendation of bamboo species in the ecology park, center for plant conservation, botanic gardens–LIPI, Bogor Regency, West Java. This study aimed to make an inventory of bamboo species to provide an identification key, a distribution map of those bamboos, as well as, a recommendation on bamboo management in the Ecology Park. The study was conducted in January-February 2019 using the exploration method, located in the Ecology Park, Center for Plant Conservation, Botanic Gardens, Campus of Cibinong Science Center–Botanic Gardens (CSC–BG), LIPI, Cibinong, Bogor, West Java. The bamboo herbarium specimens were made to determine the bamboo species found in the Ecology Park. The bamboo specimens were processed and deposited in the Herbarium Bogoriense (BO). The morphology characters of bamboo were described and to be used to determine the species and also to provide an identification key. The distribution map of bamboo in the Ecology Park created and it was overlapped with the existing map of the Ecology Park area. The bamboo management recommendation was made based on the data of bamboo inventory and mapping. The results showed that there are three species of bamboo from 40 clumps found in the Ecology Park, namely Bambusa vulgaris (bambu ampel), Gigantochloa apus (bambu tali), and G. pseudoarundinacea (bambu andong). These bamboos were alleged spontaneous collection and mostly distributed near the lake and along the road. An identification key to the species and a distribution map of bamboo species in the Ecology Park were presented. These bamboos play an important role in the Ecology Park to maintain water availability and to help to prevent a landslide. It is recommended that bamboo clumps in Ecology Park need to be tidied by making a fence and thinning of bamboo clumps needs to be done at least every 2 years. The management staff need to enrich the bamboo species in the Ecology Park, particularly ornamental and endemic bamboo of Indonesia, such as Schizostachyum brachycladum (bambu gading) and Dinochloa scandens (bambu cangkoreh), planted in accordance with the bioregion where the species come from.